PID-controlled active damping to mitigate chatter in lathe machining - Sunarya, Adhitya Sumardi; Khoirunnisa, Hilda; Lilansa, Noval; Anggraeni, Pipit; Nugraha, Nurwisma; Mumtaha, Raden Malik Hakim Muslim (Politeknik Negeri Lhokseumawe, 2025)
Chatter is a result of undesired vibration in manufacturing that damages product surfaces and reduces production efficiency. Addressing chatter requires enhancing machine-tool dynamic stability, optimizing cutting parameters, and implementing real-time monitoring and control. This study presents a PID-controlled active damping system developed through theoretical analysis, simulation, and experimental testing on LabVIEW and Arduino platforms. Orthogonal turning simulations were conducted with spindle speed of 1000 RPM, feed rate of 0.2 mm/rev, and depth of cut of 1 mm. Vibration sensors enabled rapid chatter detection, and real-time PID adjustments suppressed instability within 0.02 seconds, achieving 98.11% suppression accuracy. Data acquisition was carried out using NI DAQ USB-6218, with Arduino and LabVIEW results showing close agreement, apart from minor deviations due to communication delay. The system improved surface finish, reduced tool wear, and enhanced overall machining performance. These results show the potential of PID-based active damping as an effective solution for real-time chatter suppression and efficiency improvement in lathe machining.